Legal aid scheme in Nigeria: any deference in access to justice for persons with disabilities (2010)
This article examines the Legal Aid Scheme in Nigeria against the backdrop of its philosophy and objective of providing equal access to justice for all irrespective of financial limitations. It examines the peculiar needs of persons with disabilities and their vulnerability to poverty against the intendment of the Legal Aid Scheme to provide access to justice for all persons so that no one is excluded from access to justice by poverty. The article considers the linkages between poverty and disability and concludes that there is a great omission in the legal aid scheme in Nigeria in not specifically providing legal aid for persons with disabilities (PWDs) in the Legal Aid Act, beyond the general provisions. The article recommends that in view of the cyclic nature of disability and poverty, the Legal Aid Act should be amended to provide specifically for persons with disabilities.